Apple Juice to Reduce Total Cholesterol Level in Women Over 40 Years Old - Muallima Tulummah; Retno Sulistiyowati; Kurnia Ritma Dhanti (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2022)
Cholesterol is a fatty substance in the human body’s cells. A person who has high cholesterol levels may develop coronary heart disease (CHD), which increases their risk of developing atherosclerosis. Due to pregnancy, hormonal, and menopausal reasons, women over the age of 40 are more likely to have elevated cholesterol levels than younger women. Apples' fiber content has been shown to reduce blood cholesterol levels. This study aimed to determine the effect of apple juice on cholesterol levels. A pretest-posttest group design with a pre-experimental methodology was used in this study. 38 women between the ages of 40 and 66 made up the sample of this study. Every morning for seven days, respondents received apple juice. The study was carried out in August 2020. According to this study, apple juice has a positive effect in lowering total cholesterol levels. Prior to receiving apple juice, the mean total cholesterol level was 226.68 17.230 mg/dL, while the mean cholesterol level after apple juice treatment was 184.39 13.771 mg/dL. Total cholesterol levels before and after receiving apple juice are known to differ by 42.29 mg/dL. The Paired T-Test analysis of the data revealed a value of P = 0.000 (P 0.05), indicating that there was an effect of giving apple juice on lowering respondents' total cholesterol levels.